1992
DOI: 10.1021/bi00161a049
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen radical-mediated DNA damage by redox-active chromium(III) complexes

Abstract: The mechanism of DNA damage induced by Cr(III) complexes is currently unknown even though it is considered to be the ultimate biologically active oxidation state of chromium. In this study, we have employed the Salmonella reversion assay to identify mutagenic Cr(III) complexes. Cyclic voltammetry was used to differentiate the redox kinetics between mutagenic and selected nonmutagenic Cr(III) species. Plasmid relaxation of supercoiled DNA was employed to show in vitro interactions with plasmid DNA and correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
43
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(52 citation statements)
references
References 29 publications
(24 reference statements)
6
43
2
Order By: Relevance
“…Hence, these studies are consistent with investigations that demonstrated that mutagenic forms of trivalent Cr possessed chelating ligands containing pyridine-type N or other imine-N (e.g. 2,2k-bipyridine, phenanthroline and Schiff bases) coordinated to the metal and that they generated reactive oxygen species (Sugden et al 1992). Cr compounds that do not have imine ligands lack the DNA cleaving activity in the presence of biological reducing agents (Speetjens et al 1999b).…”
Section: Chromium Picolinatesupporting
confidence: 87%
“…Hence, these studies are consistent with investigations that demonstrated that mutagenic forms of trivalent Cr possessed chelating ligands containing pyridine-type N or other imine-N (e.g. 2,2k-bipyridine, phenanthroline and Schiff bases) coordinated to the metal and that they generated reactive oxygen species (Sugden et al 1992). Cr compounds that do not have imine ligands lack the DNA cleaving activity in the presence of biological reducing agents (Speetjens et al 1999b).…”
Section: Chromium Picolinatesupporting
confidence: 87%
“…Sugden et al 73 have employed the Salmonella reversion assay to identify mutagenic Cr(III) complexes. Relaxation of supercoiled DNA was used to show in vitro interactions with plasmid DNA.…”
Section: Chromiummentioning
confidence: 99%
“…Hydroxyl radicals ( ⅐ OH), which are generated during the cellular reduction of chromate (25) are also capable of causing DNAprotein cross-linking (26,27) and are considered as the "ultimate agents" in chromate carcinogenesis (28). Cr(III) and the reactive intermediate states of chromium may also be considered as carcinogenic because ⅐ OH radicals are shown to be generated by redox cycling of Cr(III) (29), and DNA damage has been shown to be caused by intermediate valence states of chromium, such as Cr(V) (30).…”
mentioning
confidence: 99%